KEMAMPUAN KOMUNIKASI SISWA SMP KELAS VIII DITINJAU DARI SELF-EFFICACY - Nirwanty Angela Al Ghani; Citra Megiana Pertiwi; Nelly Fitriani (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to determine whether there is a relationship between students' mathematical communication skills in terms of self-efficacy in line gradient material. This is because the achievement that students have is still relatively minimal or low. This study uses a qualitative descriptive research method with samples taken from one of the schools in Cimahi with one class of research subjects. Where the instrument that the researcher uses is a description of the student's communication ability test and non-test in the form of a self-efficacy attitude scale (questionnaire). The conclusion obtained in this study is that mathematical communication skills in terms of self-efficacy in students who have high communication skills have high self-efficacy because in mastering the concept they have met the criteria but there are also some students who have high self-efficacy but in mastery of skills. communication is still low.